Az agrár-felsőoktatás történetéből (Hensch Árpádtól A Debreceni Üzemtani Iskoláig): A magyaróvári „Nagy Tanári Kar” egyik kiválósága Hensch Árpád 1847–1913 - Tenk, Antal; Nemessály, Zsolt (Gerundium, 2015)
FROM THE HISTORY OF AGRICULTURAL HIGHER EDUCATION. his paper connects the two periods and places of Hungarian agricultural higher education. he link is the scientiic work of Árpád Hensch – professor of Academy of Agricultural Sciences in Mosonmagyaróvár at the end of the 19th century – which has a signiicant efect on the Hungarian economic higher education even nowadays. his signiicance is proven by the eforts since the 1960s in Debrecen evolved on the Department of Business Economics in the former University of Agricultural Sciences.